Hubungan Kematangan Emosi Dengan Pengambilan Keputusan Karir Siswa SMA ITP Surabaya - Juniar, Zesarizky; Mudhar, Mudhar (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
This research was carried out based on incidents at SMA ITP Surabaya and it was found that students were not yet mature in making career decisions after graduating. The aim of this research is to determine the relationship between emotional maturity and career decision making in ITP High School students with a sample size of 96 students. This research uses quantitative with a correlational design. As for the results of the correlation test which was carried out using the SPSS version 26.0 for Windows computer, the results of the correlation test (r) were 0.468 and a significant value of 0.000 (p < 0.05), which means that the relationship between these two variables can be interpreted as that the higher the emotional maturity variable, the higher the career decision making variable in students.